Chromosomal Processes in Mind-Body Medicine: Chronic Stress, Cell Aging, and Telomere Length - Esch, Tobias; Kream, Richard M; Stefano, George B (Medical science monitor basic research, 2018)
Stress affects cellular aging and inflammatory and chromosomal processes, including telomere length, thereby potentially compromising health and facilitating disease onset and progression. Stress-related diseases and strategies to manage stress usually require integrative or behavioral therapeutic approaches that also operate on cellular levels. Mind-body medicine (MBM) uses the interaction between the mind, body, behavior, and the environment to correct physical and psychological malfunctions, thus ameliorating disease states and improving health. The relaxation response (RR) is a physiological opponent of stress and the stress response (SR) (i.e., fight-or-flight response), also invoking molecular anti-stress processes. Techniques that elicit the RR are at the core of practically all MBM interventions. We surmise that these techniques can also affect chromosomal and telomere processes, molecular aging, and the modulation of inflammatory states on cellular levels.
Keywords: Telomere Homeostasis; psychický stres; Chronic Disease; homeostáza telomer; Stress, Psychological; Aging; Mind-Body Therapies; Telomere; Cellular Senescence; stárnutí; Humans; psychosomatické a relaxační terapie; lidé; relaxační terapie; chronická nemoc; telomery; stárnutí buněk; Relaxation Therapy